ประสบการณ์ที่เป็นประโยชน์จากการปรึกษาเชิงจิตวิทยาในมุมมองของผู้รับบริการ - สิรัช สุเมธกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study explored the psychological experiences of clients with significant helpful events from counseling. The reason for this is that significant events yield remarkable outcome, and there was no research regarding the topic within Thai context. Interpretative Phenomenological Analysis (IPA), a qualitative research method, was conducted on 6 participants via in-depth interviews. Three super-ordinate themes emerged. (1) Characteristics of helpful relationship, with 3 sub-ordinate themes: being able to talk, counselor’s attentiveness and common understanding, and focusing on client’s perception and consideration of internal world. (2) Key process to new understanding, with 4 sub-ordinate themes: exploring and trying to understand one’s experience, changing/challenging one’s old beliefs or understandings, trying new things or resolutions derived from sessions, and expanding one’s perspectives or alternatives. (3) Positive outcomes from counseling, with 2 sub-ordinate themes: enhancing capabilities of dealing with problems/circumstances, and self-acceptance and living in harmony with one’s problems. This study gives an overview of experiences, change mechanism, and outcomes of the clients from counseling. Literatures relevant to the study are discussed. Potential topics for further studies might be about characteristics of significant information, or about process of new understanding examined within broader contexts, or integrating concepts of first- and second-order change in counseling with significant helpful events research.